Gambaran Pengasuhan Orang Tua terhadap Anak SMA Negeri 1 Sutera di Kampung Sungai Sirah Kenagarian Surantih Kecamatan Sutera Kabupaten Pesisir Selatan - Wira Puspita Sari; Wirdatul Aini; Vevi Sunarti (Universitas Negeri Padang, 2018)
The background of this research is the motivated by good learning achievement of children, the researchers suspect this is caused by good parenting. The purpose of this study is to reveal the picture of parenting parenting in terms of (1) monitoring, (2) closeness, and (3) support, towardSMA N 1 Sutera in Kampung Sungai Sirah Kenagarian Surantih Kecamatan Sutera Pesisir Selatan Regency. The type of research is descriptive quantitative. The population is 35 people with 20 samples. Sampling technique stratified random sampling. Techniques of data collection are questionnaires and techniques of data analysis using the percentage calculations. Based on the result of the research, it is found that (1) the picture of parent monitoring on the behavior of SMA N 1 Sutera Children in Kampung Sungai Sirah is said to be good, (2) the image of parents closeness to SMA N 1 Sutera Children in Kampung Sungai Sirah is said to be good, (3) the support of parents to SMA N 1 Sutera in Kampung Sungai Sirah is said to be good. Suggestion for parenting of SMA N 1 Sutera Children in Kampung Sungai Sirah is further improved.